Self Efficacy Terhdap Kepatuhan Perawatan Diri Pada Penderita Hipertensi - Andi Muthiyah A. AM; Viyan Septiyana Achmad; Isymiarni Syarif; Jukarnain Jukarnain; Titin Supriatin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
This study aims to investigate the relationship between self-efficacy and self-care adherence in patients with hypertension. Self-care adherence refers to an individual's compliance with medical recommendations and behaviors supporting hypertension control. The research method employed is an observational study involving participants with hypertension. Data were obtained through questionnaires measuring the level of self-efficacy and self-care adherence. Statistical analysis was conducted to identify the relationship between self-efficacy and self-care adherence. The findings of the study indicate a positive relationship between self-efficacy and self-care adherence in patients with hypertension. Individuals with strong self-efficacy are more likely to be compliant in their self-care practices, including regularly taking medication, following a healthy diet, engaging in regular exercise, and monitoring their blood pressure. These findings highlight the importance of strengthening self-efficacy in individuals with hypertension to enhance their self-care adherence. In conclusion, self-efficacy plays a significant role in self-care adherence among patients with hypertension. Enhancing self-efficacy can be an effective strategy for improving self-care adherence and controlling blood pressure in patients with hypertension